Combined effect of inter-arm systolic blood pressure difference and carotid artery plaque on cardiovascular diseases and mortality: A prospective cohort study - Yun, Cuijuan; Xin, Qian; Zhang, Sijin; Chen, Shuohua; Wang, Jianli; Wang, Chi; Wang, Miao; Zhao, Maoxiang; Sun, Yizhen; Hou, Ziwei; Wu, Shouling; Xue, Hao (Frontiers in Cardiovascular Medicine, 2022)
Objectives Previous studies have confirmed the relations between inter-arm systolic blood pressure difference (IASBPD) and carotid artery plaque with the risk of cardiovascular diseases (CVD). But it is unclear whether the combined effect of IASBPD and carotid artery plaque further increases the risk of CVD and all-cause mortality. Materials and methods We enrolled 4,970 participants (≥40 years old) in the prospective Kailuan study. All participants underwent dual-arm blood pressure and carotid artery ultrasounds. IASBPD was the absolute value of the difference between dual-arm blood pressure. All the participants were divided into four groups according to their IASBPD levels and the presence or absence of carotid artery plaque and Cox proportional hazards models were used to calculate the hazard ratios (HRs) and 95% confidence interval (CI) for incident CVD and all-cause mortality. Results During a median follow-up of 7 years, 179 CVD events and 266 deaths occurred. Multivariable Cox Regression showed that participants with IASBPD ≥ 10 mmHg and plaque had a significantly higher incidence of CVD, cerebral infarction (CI), and myocardial infarction (10, 7.27, and 1.36%, respectively). After adjusting for covariates, the IASBPD ≥ 10 mmHg and carotid plaque group significantly increased risks for CVD (HR 2.38; 95% CI, 1.40∼4.05), CI (HR, 2.47; 95% CI, 1.31∼4.67), and all-cause mortality (HR, 2.08; 95% CI, 1.20∼3.59). Conclusion Our study indicated that the combination of IASBPD and carotid artery plaque was associated with incident CVD and all-cause mortality.